A Case Study on General Motors - Dasgupta, Dr. Pooja; Dubey, Ms. Khushbu (IJRDO - Journal of Social Science and Humanities Research, 2016)
General Motors was founded by William C. Durant in 1908, in Flint, Michigan. GM acquired Oldsmobile later that year. In 1909, Durant brought in Cadillac, Oakland and Elmore. In 1909, GM acquired the Reliance Motor Truck Company of Owosso and the Rapid Motor Vehicle Company of Pontiac, both of Michigan. Because of the large amount of debt taken on in its acquisitions and loss due to collapse in new vehicle sales, Durant lost control of GM in 1910 to a bankers' trust.